Simulation of thermal conductivuty of polymer composites based on poly(methyl methacrylate) with different types of fillers - Дінжос, Роман Володимирович; Лисенков, Едуард Анатолійович; Фіалко, Наталія Михайлівна (Eastern-European Journal of Enterprise Technologies, 2015)
The results of investigating the influence of fillers of different nature on the thermal conductivity of polymer composites are widely presented in modern scientific works of many authors. However, there has been little analysis of the obtained data within existing percolation models of thermal conductivity. Using mathematical simulation allows to improve the methods of manufacturing composites and manage the properties in a wide range. The paper presents the results of experimental and numerical studies of thermal conductivity of poly(methyl methacrylate) and composites containing aerosil, carbon nanotubes, iron oxide and dispersed aluminum particles. The influence of the type and size of fillers on the features of thermal conductivity of the studied polymer composites was investigated. It was found that in the studied systems, there is a typical percolation transition, which is associated with the formation of the filler particles of "continuous" cluster. It was revealed that the lowest percolation threshold is observed for aerosil-filled composites. After reaching the percolation threshold, thermal conductivity for a system based on poly(methyl methacrylate) and carbon nanotubes increases threefold. Mathematical simulation of the percolation behavior of thermal conductivity of polymer composites within the basic theoretical models was carried out. It was shown that using the McLachlan’s allows to accurately predict the value of the thermal conductivity coefficient for polymer composites. The investigated polymer composites based on poly(methyl methacrylate) can be used as materials for creating products of the thermal power complex.